Epidemiology of potato quarantine diseases in Ukraine and Europe - Stoyanova , K. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. Analysis and data generalization on the epidemiological situation of quarantine potato diseases in Ukraine and Europe. Main pathogens determination which these diseases cause. Their spread and impact on yields evaluated, together with identification of prevention and control measures to ensure food security in the agricultural sector.Methods. The spread of potato diseases and their incidence of plants and tubers were studied using an information and analytical method based upon the data analysis from the Department of phytosanitary safety of the State Service of Ukraine on Food Safety and Consumer service for 2019—2023 and on the basis of the EPPO Global Database Protocol.Results. The most spread potato quarantine diseases were: potato wart (Synchytrium endobioticum), brown rot of potato (Ralstonia solanacearum), ring rot (Clavibacter michiganensis), blackleg of potato (Dickeya dianthicola) and potato spindle viroid (Potato spindle tuber pospiviroid). Global trade of defeated seeds, non-following crop rotation, non-effective monitoring and control system and also climatic changes are also basic favorable factors for potato quarantine disease spread. Existing methods analysis for combating quarantine diseases has shown that the most effective are integrated approaches that include the use of resistant varieties, biological protection preparations and regular monitoring of the state of crops.Conclusions. The received results witnessed about the strengthening quarantine measures in Ukraine and European countries. The strengthening phytosanitary measures, developing and improving resistant varieties, international cooperation experience and technologies exchange are basic part for successful struggle with quarantine diseases. The above-mentioned measures realization will favor the potato quarantine diseases spread, yield increase and quality production increase. It will also help the food security improving European and Ukrainian agrarian sectors development.